2021
DOI: 10.3389/fneur.2021.719329
|View full text |Cite
|
Sign up to set email alerts
|

Non-stenotic Carotid Plaques in Embolic Stroke of Unknown Source

Abstract: Embolic stroke of unknown source (ESUS) represents one in five ischemic strokes. Ipsilateral non-stenotic carotid plaques are identified in 40% of all ESUS. In this narrative review, we summarize the evidence supporting the potential causal relationship between ESUS and non-stenotic carotid plaques; discuss the remaining challenges in establishing the causal link between non-stenotic plaques and ESUS and describe biomarkers of potential interest for future research. In support of the causal relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 156 publications
(153 reference statements)
1
17
0
Order By: Relevance
“…The carotid area is easily accessible for non-invasive studies and is relatively accurate. Carotid plaque plays a major role in the occurrence of cerebrocardiovascular disease ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The carotid area is easily accessible for non-invasive studies and is relatively accurate. Carotid plaque plays a major role in the occurrence of cerebrocardiovascular disease ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another larger clinical study demonstrated that only 3.4% of ESUS patients were diagnosed clinically with AF during the trial follow-up period [ 20 ]. Similarly, studies have shown that 5–9% of ESUS patients with non-stenotic carotid plaque have PFO [ 21 ]. Our study was a cross-sectional study without long-term follow-up and we did not perform transesophageal ultrasonography in the patient screening, the impact of non-stenotic carotid plaque on ESUS might be overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of independent variables to include in the multivariable models was based on available evidence of association with atherosclerosis. 24,25 Considering our previous work suggesting that the presence of high-risk features is not dependent on plaque severity, we did not include plaque severity in the model to predict baseline plaque vulnerability. 15 However, we considered the baseline ipsilateral plaque severity score and the baseline ipsilateral plaque vulnerability in the logistic regression model to predict plaque progression at 5 years and explored the interaction with log IL-6.…”
Section: Methodsmentioning
confidence: 99%